Alkaline Hydrogen Oxidation Reaction Catalysts: Insight into Catalytic Mechanisms, Classification, Activity Regulation and Challenges. Issue 4 (1st February 2023) - Mu, Xueqin; Liu, Suli; Chen, Lei; Mu, Shichun
Abstract : Hydrogen oxidation reaction (HOR) is an important semi‐cell reaction in the renewable energy conversion technology such as fuel cells. However, due to the slow reaction rate, the development of highly active catalysts remains a major challenge in alkaline fuel cells. Based on fundamental understanding of the sluggish kinetics toward the reaction mechanism in alkaline electrolytes, noble and non‐noble metal catalysts and their regulation strategies including geometry, composition, atom‐doping, oxyphilic site and substrate engineerings are analyzed and summarized in this review to seek for the possible breakthrough toward HOR catalytic performance enhancement. Eventually, challenges and opportunities faced by alkaline HOR, and potential future research trends are proposed. This review not only deepens the understanding of the hydrogen electrocatalysis mechanism, but also provides guidelines for the rational design of advanced HOR catalysts. Abstract : Recent progress on fundamental understandings of hydrogen oxidation reaction (HOR) mechanisms and advanced HOR electrocatalysts is summarized, the optimization strategy engineering of HOR catalysts for adsorption intermediates and reaction barrier regulation is discussed to provide new insights and directions for the development of electrocatalytic reconstruction engineering in the future.